Increasing Students' Critical and Creative Thinking Skills using the Hybrid-PjBL Learning Model in Bima Local Wisdom-Based History Learning - Faidin Faidin; Suharti Suharti; Muhammad Subhan; Fajrun Fajrun; Buhari Buhari (Universitas Muhammadiyah Mataram, 2024)
Local wisdom based learning is very necessary in developing 21st century skills (Critical Thinking, Creativity, Collaboration, and Communication). Its implementation in History learning greatly influences how students determine topics, explore information, collect and compile information results in the form of poster products which are then communicated to get responses and feedback for project improvement. The research aims to describe Increasing Students' Critical and Creative Thinking Skills Using the Hybrid-PjBL in Bima Local Wisdom-Based History Learning. This study uses an experimental research method, quasi-experimental design. because the researcher considered that the study ignored external variables that could affect the results of the study. Then the researcher wanted to identify the differences in the learning process using the Hybrid-PjBL model with the conventional model on students' critical and creative thinking skills, and the grouping of experimental and control groups that are not selected randomly. The sample selection technique uses purposive sampling. The research sample was 188 students in KAE High School, 94 people in the experimental class and 94 people in the control class. Data analysis in this study includes normality tests and non-parametric statistical tests using SPSS. The results of the hypothesis test, if a significant value is obtained (2-tailed) <α = 0.05, then H0 will be rejected or Ha is accepted. conversely, if sig. (2-tailed) > α = 0.05, then H0 is accepted or Ha is rejected. The research instrument uses tests, and questionnaires that have been tested and validated by expert judgment. Quantitative data processing, through descriptive analysis (mean, median, mode, minimum and maximum values, percentage and frequency), normality test, and hypothesis test, finally Mann Whitney U Test and Wilkson Test. The results of the study showed that the experimental class was significantly higher than the control class. The Mean and Standard Deviation values in the pretest and posttest of the experimental class were 65.28 and 85.32 and the control class were 69.27 and 73.56. Specifically for the Experimental Class in the Mann-Whitney U Asymp value. Sig. (2-tailed) test results were 0.01 on the pre-test and post-test values of critical and creative thinking. 0.01 is smaller than 0.05, the alternative hypothesis is accepted. This means that the implementation of the Hybrid PjBL model in improving critical and creative thinking skills is very good.